1978
DOI: 10.1021/i260068a019
|View full text |Cite
|
Sign up to set email alerts
|

Settling of Coal in Coal-Oil Slurries

Abstract: This study investigates the settling phenomenon of coal-oil solids as a function of solids concentration, initial slurry height, settling container diameter, temperature, chemical treatment, and application of ultrasonic radiation. Mathematical correlations developed by Michaels and Bolger were utilized in the analysis of the data and were found to be applicable for this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…At present the maximum relative error of Equation (6) is 5.5% at ja ¼ 1, and 12% at ja ¼ 0.1. (5). It can satisfy this condition.…”
Section: Settling Under Gravitymentioning
confidence: 93%
See 2 more Smart Citations
“…At present the maximum relative error of Equation (6) is 5.5% at ja ¼ 1, and 12% at ja ¼ 0.1. (5). It can satisfy this condition.…”
Section: Settling Under Gravitymentioning
confidence: 93%
“…The values of zeta potential for coal particles in the oil are approximately more than 30 mv (see Table 4). Interparticle electrostatic interaction energy can be expressed as [5] …”
Section: Settling Under Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…They experimentally verified the relations using kaolin suspensions. More recently, Slagle et al (1978) have demonstrated the application of these settling rate equations in the dilute and intermediate concentration regions to coal in COM's. They remarked that the rate law would change from the intermediate to dilute approximations as the temperature is raised at constant particle concentration.…”
Section: Introductionmentioning
confidence: 99%